THE COVID-19 PANDEMIC TOWARD BUYING BEHAVIOR FOR E-COMMERCE AMONG HOUSEHOLDS IN MALAYSIA - Kumar, Dhanonjoy; Bhuiyan, Abul Bashar; Haque, Tasnuba; Ali, Jafor; Uddin, Md. Kamal (International Journal of Business and Management Future, 2022)
The COVID-19 epidemic has altered many people's lifestyles and incentives, causing their shopping habits to shift. The current study aims to evaluate these changes. In order to achieve this aim, the study analyzed the influence of the pandemic on Buying Behavior for e-commerce transaction across industries in order to discover household preferences. The present study is intended to respond to research questions of quantitative and qualitative nature. Data collection and analysis techniques from both methods were implemented. Regression analysis was used to study situations in which variables were dependent and simultaneously influenced by several independent variables. The study found that buying behavior is influenced by a number of characteristics, including mental health, isolation, lockdown, price sensitivity, and financial distress. The study also found four factors have a positive association with the dependent variable, whereas the remaining one factor has no relationship with the dependent variable. The world economy, and particularly international trade, have suffered and continue to suffer huge losses as a result of the Coronavirus Epidemic. The uncertainty in which enterprises and end customers have found themselves is exacerbated by a number of issues. These include, to mention a few, income loss, cross-border travel limitations, evolving consumer demand, and changing market actor behavior.JEL Classification Codes: D10, L81, Q12.